The branchial microbiome and Neoparamoeba perurans infection - Slinger, JC (2022)
Amoebae are unicellular protists distributed throughout terrestrial and aquatic environments. Commonly known as bacterivores or detritivores, members of the Amoebozoa group can parasitise higher vertebrate hosts and cause infectious disease. Furthermore, the virulence of such amoebic infections can in some cases be mediated by the presence of specific bacterial cofactors at the host-pathogen interface. Amoebic gill disease (AGD) remains one of the most significant diseases affecting the productivity of Atlantic salmon (Salmo salar L.) aquaculture, incurring significant costs to the Australian salmonid industry. The aetiological agent Neoparamoeba perurans is a free-living marine amoeba, which colonise gill mucosal surfaces eliciting often fatal branchialitis in affected fish. Although Koch's postulates have been established for AGD, N. perurans is a multi-organism complex of amoeba, a kinetoplastid endosymbiont and associated bacterial consortia. Determination of virulence factors that underpin AGD pathogenesis is therefore complicated by the potential interplay between these organisms. Additionally, commensal or pathogenic microbes that simultaneously colonise the host gill could potentially influence the course of AGD. Bacteria and N. perurans inhabit the same ecological niche, sharing resources and space on the gill surface, although the dynamics of microbial communities in the context of AGD remain largely unknown. It was hypothesised that the type and abundance of bacterial taxa present may ultimately affect amoebic-host interactions. Therefore, the aim of this thesis was to characterise the gill mucus community in the context of AGD pathogenesis. To investigate whether non-culturable bacteria may influence the course of AGD, methods and bioinformatic pipelines to accurately profile branchial bacterial communities required initial refinement and validation. Chapter 2 compared sampling techniques and preservatives and tissue collection strategies. Results indicated that non-terminal mucus swabbing of the ...